Factors Influencing Amount of Weekly Exercise Time in Colorectal Cancer Survivors. Issue 3 (May 2017) - Chou, Yun-Jen; Lai, Yeur-Hur; Lin, Been-Ren; Liang, Jin-Tung; Shun, Shiow-Ching
Abstract : Background: Performing regular exercise of at least 150 minutes weekly has benefits for colorectal cancer survivors. However, barriers inhibit these survivors from performing regular exercise. Objectives: The aim of this study was to explore exercise behaviors and significant factors influencing weekly exercise time of more than 150 minutes in colorectal cancer survivors. Methods: A cross-sectional study design was used to recruit participants in Taiwan. Guided by the ecological model of health behavior, exercise barriers were assessed including intrapersonal, interpersonal, and environment-related barriers. A multiple logistic regression was used to explore the factors associated with the amount of weekly exercise. Results: Among 321 survivors, 57.0% of them had weekly exercise times of more than 150 minutes. The results identified multiple levels of significant factors related to weekly exercise times including intrapersonal factors (occupational status, functional status, pain, interest in exercise, and beliefs about the importance of exercise) and exercise barriers related to environmental factors (lack of time and bad weather). No interpersonal factors were found to be significant. Conclusions: Colorectal cancer survivors experienced low levels of physical and psychological distress. Multiple levels of significant factors related to exercise time including intrapersonal factors as well as exercise barriers related to environmental factors should be considered. Implications for Practice: Healthcare providers should discuss with their patients how to perform exercise programs; the discussion should address multiple levels of the ecological model such as any pain problems, functional status, employment status, and time limitations, as well as community environment.